Recurrence of bilateral atypical femoral fractures associated with the sequential use of teriparatide and denosumab: a case report. Issue 2 (February 2016) - Ramchand, S.; Chiang, C.; Zebaze, R.; Seeman, E.
Abstract We report that a postmenopausal woman with osteoporosis developed bilateral incomplete atypical femoral fractures (AFFs) after seven years of bisphosphonate therapy. Cessation of the bisphosphonate and treatment with teriparatide was associated with near complete radiological resolution of the AFFs. After 12 months without treatment, denosumab was commenced to prevent structural deterioration. Six months later she developed recurrent bilateral AFFs. This case highlights the management dilemma in patients with ongoing bone loss but prone to stress fractures associated with antiresorptive therapy. Stopping the antiresorptive is recommended but structural decay will recur predisposing to fragility fractures. If the antiresorptive is continued, bone material composition will be further compromised predisposing to atypical fractures. Teriparatide may assist healing of stress fractures and improvement in bone matrix composition. Later antiresosrptive therapy to preserve bone microstructure may compromise material composition.